Cultivation Of Chlorella Vulgaris Using Organic Fertilizer As Nutrient Source For Biodiesel， Maltodextrin Production And Co2-Biomitigation - Lam, Man Kee (2014)
In the present study, attempt was made to solve the problems by cultivating Chlorella vulgaris using organic fertilizer (derived from compost) instead of depending on chemical fertilizer. Under the supplement of organic nutrients, it was found that Chlorella vulgaris grown favourably with 100 mL of organic fertilizer medium (or corresponded to nitrate content of 26.67 mg/L), 24 hours of continuous illumination and pH of 5. About 0.50 g/L of biomass yield was attained after 12 days of cultivation. Increasing the CO2 concentration to the cultivation could accelerate the growth of Chlorella vulgaris, however, reducing the CO2 removal efficiency. The highest CO2 removal efficiency, 92.2 %, was achieved by using atmosphere air (0.03 % of CO2). By using Bligh and Dyer extraction solvents (methanol to chloroform volume ratio of 2:1), about 18 % of lipid can be extracted from the dried Chlorella vulgaris biomass. The lipid was mainly comprised of unsaturated fatty acids, such as C18:1, C18:2 and C18:3. Through transesterification reaction parametric study, about 95 % of fatty acid methyl ester (FAME) or biodiesel was attained under the following conditions: methanol to THF to lipid molar ratio of 60:15:1, H2SO4 concentration of 21 wt.%, temperature of 60 °C and reaction time of 3 hours. In addition, the carbohydrate left over in the lipid-extracted microalgae biomass residues was successfully recovered for maltodextrin production (co-product).